Composite solid electrolyte and preparation method and application thereof
By using composite solid electrolytes in lithium-ion batteries, distributing lithium supplement materials and forming preset shapes, the problem of increasing impedance of the positive electrode material caused by the deliquification reaction of lithium supplement materials is solved, and the battery is efficiently supplemented with lithium supplements and long cycle life is achieved.
Patent Information
- Application Number
- CN202411976638.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-11
AI Technical Summary
During the first charging and discharging process of lithium-ion batteries, the deliquency reaction of lithium-ion materials leads to an increase in the impedance of the positive electrode material, affecting the cycle life and energy density of the battery.
Using composite solid electrolyte, by distributing lithium supplement material in the solid electrolyte matrix and forming a preset shape, the lithium supplement material deliquification product is prevented from accumulating in the positive electrode material, thereby avoiding an increase in impedance.
It effectively avoids the problem of increasing impedance of the positive electrode material caused by the deliquification products of lithium supplement materials, improves the utilization rate of lithium supplement materials, extends the cycle life of the battery, and improves the overall electrochemical performance of the battery.
Smart Images

Figure CN119812526A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and in particular relates to a composite solid electrolyte and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used in mobile phones, iPads, laptops, automobiles and other fields due to their advantages such as high operating voltage and energy density, low self-discharge level, no memory effect, no heavy metal pollution such as lead and cadmium, and ultra-long cycle life.
[0003] During the first charge and discharge process of a lithium-ion battery, the electrode material and the electrolyte will react at the solid-liquid interface to form a solid electrolyte membrane (SEI membrane). This process will irreversibly consume the lithium ions released from the positive electrode material, causing a huge capacity loss of the lithium-ion battery, resulting in a decrease in coulomb efficiency, which directly affects the cycle life and energy density of the lithium-ion battery. In response to this phenomenon, the current solution is to add appropriate lithium-supplementing materials to the positive electrode material, and reduce the lithium loss during the cycle by releasing active lithium through the decomposition of the lithium-supplementing materials during battery charging.
[0004] However, when lithium-supplementing materials and positive electrode materials are compounded, since the lithium-supplementing materials are sacrificial lithium salts, they will be delithiated and decomposed during the first charge. The inorganic fillers produced after the delithiation are usually inactive substances. These inactive substances accumulate in the positive electrode materials, resulting in a significant increase in the overall impedance of the positive electrode materials. At the same time, the delithiation reaction directly leads to a reduction in the volume of the lithium-supplementing materials, and even further pulverization. This volume change of the lithium-supplementing materials is the direct cause of pits on the surface of the positive electrode sheet and voids inside the positive electrode sheet after the first charge. The presence of these pits and voids destroys the original continuity of the positive electrode material, which in turn causes the overall impedance of the positive electrode material to increase further, and has an adverse effect on the overall structural stability of the electrode sheet. This increase in the impedance of the positive electrode material has a direct and significant impact on the overall impedance of the battery, which seriously restricts the performance of the battery. Summary of the invention
[0005] The purpose of the present application is to provide a composite solid electrolyte and a preparation method and application thereof, aiming to solve the problem of increased impedance of the positive electrode material after the lithium supplement material is consumed.
[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0007] In a first aspect, the present application provides a composite solid electrolyte, comprising a solid electrolyte matrix and a lithium supplement material distributed in the solid electrolyte matrix, wherein the solid electrolyte matrix and the lithium supplement material are combined to form a preset shape;
[0008] The chemical formula of the lithium supplement material is Li x M y O z , wherein M includes transition metal elements, 1≤x≤8, 0<y, 0<z<7.
[0009] In a second aspect, the present application provides a method for preparing a composite solid electrolyte, comprising the following steps:
[0010] preparing an electrolyte slurry containing a lithium supplement material and a solid electrolyte matrix precursor;
[0011] The electrolyte slurry is solidified so that the lithium supplement material is distributed in the solid electrolyte matrix and forms a preset shape, thereby obtaining a composite solid electrolyte.
[0012] In a third aspect, the present application provides a secondary battery comprising a positive electrode material, a negative electrode material and a solid electrolyte layer, wherein the solid electrolyte layer comprises the composite solid electrolyte provided in the first aspect or the composite solid electrolyte obtained by the preparation method provided in the second aspect.
[0013] The composite solid electrolyte provided in the first aspect of the present application is that the lithium supplement material is distributed in the solid electrolyte matrix, and the solid electrolyte matrix and the lithium supplement material can be integrated to form a preset shape. When the composite solid electrolyte is applied to the battery system, it can not only play the role of ion conduction, but also form a conductive path inside the battery to ensure the ion transmission during the normal charge and discharge process of the battery. During the first charge and discharge cycle of the battery, the lithium supplement material can release lithium ions to compensate for the irreversible lithium loss in the battery system, thereby playing a role in lithium supplement. In particular, since the lithium supplement material and the positive electrode material are separated from each other, the lithium depletion product of the lithium supplement material will not accumulate in the positive electrode material, thereby effectively avoiding the problem of the increase in the impedance of the positive electrode material caused by the lithium supplement material depletion product, and the lithium supplement material depletion product such as inorganic filler will also be distributed in the solid electrolyte matrix, and these inorganic fillers can form a reinforced network inside the solid electrolyte matrix, thereby better maintaining the structural integrity of the composite solid electrolyte. At the same time, the environment in which the lithium supplement material is located during the lithium depletion and lithium supplement process is more stable, and the lithium supplement material can more fully play the role of lithium supplement, thereby improving the utilization rate of the lithium supplement material.
[0014] The preparation method of the composite solid electrolyte provided in the second aspect of the present application is to mix the lithium replenishing material with the solid electrolyte matrix precursor to form an electrolyte slurry, and during the curing process, the lithium replenishing material is distributed in the solid electrolyte matrix and forms a preset shape, thereby effectively preparing a composite solid electrolyte having the properties of the composite solid electrolyte of the present application as described above. In addition, the preparation method of the composite solid electrolyte of the present application is conducive to obtaining a composite solid electrolyte with a stable structure, which can not only give full play to the role of ion conduction, but also give full play to the role of lithium replenishment, realize efficient lithium replenishment of the battery, and is conducive to wide application.
[0015] The secondary battery provided in the third aspect of the present application contains the composite solid electrolyte of the present application, so that the obtained secondary battery has the characteristics of high capacity, high initial efficiency and long cycle, improves the overall electrochemical performance of the battery, and is conducive to wide use. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0017] Figure 1 is a side view of a composite solid electrolyte provided in an embodiment of the present application;
[0018] Figure 2 is a top view of a composite solid electrolyte provided in an embodiment of the present application;
[0019] Figure 3 It is a schematic diagram of the trajectory of the opening structure provided in the embodiment of the present application.
[0020] Among them, the reference numerals in the figure are:
[0021] 10. Composite solid electrolyte, 20. Support part, 30. Lithium supplement part, 31. Pores. DETAILED DESCRIPTION
[0022] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0023] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0024] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0025] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0026] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0027] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0028] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0029] In the embodiments of the present application, SEI film is the abbreviation of "solid electrolyte interface", which refers to a solid electrolyte interface membrane with the characteristics of a solid electrolyte, that is, during the first charge and discharge process of a liquid lithium-ion battery, the electrode material and the electrolyte react at the solid-liquid interface to form a passivation layer covering the surface of the negative electrode material.
[0030] In a first aspect, an embodiment of the present application provides a composite solid electrolyte, including a solid electrolyte matrix and a lithium supplement material distributed in the solid electrolyte matrix, wherein the solid electrolyte matrix and the lithium supplement material are combined to form a preset shape;
[0031] The chemical formula of the above lithium supplement material is Li x M y O z , wherein M includes transition metal elements, 1≤x≤8, 0<y, 0<z<7.
[0032] Exemplarily, the transition metal element includes at least one of Fe, Ni, Mn, Cu, Zn, Co, Cr, Zr, Sb, Ti, V, Mo, and Sn. In a specific embodiment, the lithium supplement material may be Li5FeO4, Li6MnO4, Li6CoO4, Li6ZnO4, Li2NiO2, Li2CuO2, Li2CoO2, Li2MnO2, Li2Ni 0.5 Mn 1.5 O4、Li2Ni d Cu (1-d) At least one of O2 (0<d<1), etc.
[0033] It is understandable that the lithium supplement material is the main body for lithium supplementation, can play the role of lithium supplementation, and can be used as a "sacrificial agent" in the first cycle of charging to release all the lithium ions contained in the lithium supplement material at one time as much as possible to supplement the irreversible lithium ions consumed by forming the SEI film, thereby increasing the first charging capacity of the battery. This application does not limit the specific type of lithium supplement material.
[0034] It is understandable that the solid electrolyte matrix is composed of a solid electrolyte, which is one of the materials used to form a battery. In the prior art, the role of solid electrolytes in batteries is mainly to isolate positive and negative electrodes and transmit lithium ions, and is usually used in solid-state batteries. In the present application, the solid electrolyte matrix not only isolates positive and negative electrodes and transmits lithium ions, but also can load lithium replenishment materials to achieve efficient lithium replenishment.
[0035] In one embodiment, the lithium-replenishing material is mixed in the solid electrolyte matrix. Mixing refers to the mixing and doping of two or more different substances so that they blend with each other at the microscopic or macroscopic level to form a composite material. In this article, mixing means that the particles of the lithium-replenishing material are dispersed in the solid electrolyte matrix to form a composite material system.
[0036] The preset shape can be formed by integration, which usually refers to combining two or more different materials, components or processes closely together through physical, chemical or mechanical methods to form a whole with unified function and structure. In this article, the integration of the solid electrolyte matrix and the lithium supplement material means combining the two originally relatively independent parts, the solid electrolyte matrix and the lithium supplement material, into a single, collaborative entity, that is, a composite solid electrolyte with a preset shape.
[0037] In the technical solution of the present application, by distributing the lithium supplement material in the solid electrolyte matrix, and the solid electrolyte matrix and the lithium supplement material can be integrated to form a preset shape, from a physical point of view, the lithium supplement material and the lithium de-lithiation product of the lithium supplement material can be prevented from falling off from the solid electrolyte matrix. From a chemical point of view, the solid electrolyte matrix can provide a relatively stable chemical environment for the lithium supplement material, which can not only isolate the contact between the external environment and the lithium supplement material to a certain extent, so that the lithium supplement material is not easily corroded or chemically reacted, but also enable the lithium supplement material to undergo a lithium de-lithiation reaction in a relatively stable environment, which is conducive to the orderly progress of the lithium de-lithiation process of the lithium supplement material, thus effectively extending the service life of the lithium supplement material and improving the capacity utilization rate of the lithium supplement material. Therefore, when the composite solid electrolyte is applied to the battery system, the lithium supplement material is fixed in the solid electrolyte matrix, and the lithium de-lithiation product of the lithium supplement material is also fixed in the solid electrolyte matrix. In this way, the lithium supplement material and the positive electrode material are placed separately, and the lithium de-lithiation product of the lithium supplement material will not accumulate in the positive electrode material, thereby effectively avoiding the problem of the increase of the impedance of the positive electrode material caused by the lithium de-lithiation product of the lithium supplement material.
[0038] In addition, on the one hand, the good ion conductivity of the solid electrolyte matrix itself can be utilized, so that the lithium ions generated by the lithium replenishing material during the delithiation process can be transmitted through the solid electrolyte matrix at a faster speed. This fast ion transmission environment effectively promotes the delithiation process of the lithium replenishing material, so that the lithium replenishment efficiency is significantly improved, and efficient lithium replenishment is achieved; on the other hand, the lithium replenishing material is distributed in the solid electrolyte matrix, which means that the delithiation products of the lithium replenishing material, such as inorganic fillers, are also distributed in the solid electrolyte matrix. These inorganic fillers can form a reinforced network inside the solid electrolyte matrix, thereby better maintaining the structural integrity of the solid electrolyte matrix, which helps the composite solid electrolyte to play the role of ion conduction and isolation of positive and negative electrodes, and also makes the environment of the lithium replenishing material in the process of delithiation and lithium replenishment more stable, and the lithium replenishing material can more fully play the role of lithium replenishment, thereby improving the utilization rate of the lithium replenishing material.
[0039] In some embodiments, the composite solid electrolyte is divided into a supporting portion and a lithium replenishing portion where a lithium replenishing material is distributed, and the lithium replenishing portion and the supporting portion are stacked on each other.
[0040] Normally, an electrolyte is provided between the positive electrode plate and the negative electrode plate. The electrolyte, as a medium for ion transmission, can enable the positive and negative ions inside the battery to move between the positive and negative electrodes, thereby forming a current path to ensure the normal charging and discharging process of the battery. In addition, the electrolyte also has the function of isolating the positive and negative electrodes to prevent short circuits. Therefore, the composite solid electrolyte is divided into a support and a lithium supplement part. The support part may contain only a solid electrolyte matrix, and may also optionally include a conductive agent, which functions to isolate the positive and negative electrodes to prevent the positive and negative electrodes from directly contacting and causing a short circuit; the lithium supplement part contains a lithium supplement material and a solid electrolyte matrix, so that the lithium supplement material is placed separately from the positive electrode material, thereby effectively avoiding the problem of increased impedance of the positive electrode material caused by the lithium supplement material delithiation product, and the lithium supplement material delithiation product will also be fixed in the lithium supplement part, which is more conducive to maintaining the structural integrity of the composite solid electrolyte.
[0041] In one embodiment, the lithium supplement part is arranged in a plane, that is, the lithium supplement part has a uniform and flat appearance as a whole, and there is no obvious undulation or concave-convex change perpendicular to the thickness direction of the lithium supplement part, forming a completely continuous and smooth plane. At this time, the lithium supplement material and the positive electrode material are arranged separately.
[0042] In another embodiment, the lithium replenishing part is configured as an open-pore structure, and the pores contained in the open-pore structure are used to accommodate and / or contact the positive electrode material. This configuration can effectively increase the specific surface area of the lithium replenishing part, so that the contact area between the solid electrolyte matrix and the positive electrode material is effectively increased. Therefore, configuring the lithium replenishing part as an open-pore structure can effectively increase the contact area between the solid electrolyte matrix and the positive electrode material, enhance the interface adhesion between the solid electrolyte matrix and the positive electrode material, and thus effectively increase the lithium ion transmission rate, and significantly improve the charge and discharge performance and energy density of the battery.
[0043] See also Figure 1 , as a side view of an exemplary composite solid electrolyte, the composite solid electrolyte 10 includes a support portion 20 and a lithium replenishing portion 30, and the lithium replenishing portion 30 is stacked on the surface of the support portion 20, and the lithium replenishing portion 30 is arranged in a plane.
[0044] See also Figure 2 As a top view of an exemplary composite solid electrolyte, the composite solid electrolyte 10 includes a support portion 20 and a lithium replenishing portion 30. The lithium replenishing portion 30 is stacked on the surface of the support portion 20. At this time, the lithium replenishing portion 30 is arranged in an open-pore structure, specifically, the lithium replenishing portion includes a pore 31.
[0045] In one embodiment, the pores in the open-pore structure may be straight pores, curved pores, branched pores, or network-like pores. It should be noted that the pores in the open-pore structure may also form through pores along the thickness direction of the lithium supplementing portion.
[0046] In some embodiments, the shape of the pore walls in the open-pore structure includes at least one of a strip shape and a rod shape.
[0047] The lithium supplement part is an open-pore structure, that is, a pore is formed inside the lithium supplement part, and the pore wall is a structural part that maintains the shape and boundary of the pore. It can be understood that the pore wall is the boundary part of the pore, and the pore wall can outline the spatial range of the pore.
[0048] The pore walls are arranged in strip or rod shapes, so that the lithium replenishing part has a larger specific surface area, that is, the solid electrolyte matrix contacts the positive electrode material in a larger range, so that the contact area between the solid electrolyte matrix and the positive electrode material is significantly increased, which not only shortens the lithium ion transmission path between the composite solid electrolyte and the positive electrode material, but also enhances the interface adhesion between the positive electrode material and the electrolyte, thereby effectively improving the lithium ion transmission rate and significantly improving the battery's charge and discharge performance and energy density; it also enables the lithium ions generated by the lithium replenishing material to be more evenly transmitted to all parts of the positive electrode material, thereby improving the uniformity of the lithium replenishing effect; at the same time, the open pore structure of this shape has a certain flexibility, which can better adapt to the volume change of the positive electrode material during the charge and discharge process, thereby helping to improve the stability of the contact effect between the composite solid electrolyte matrix and the positive electrode material, which not only helps to improve the battery's energy density and cycle performance, but also helps to maintain the continuity of the lithium replenishing process and extend the lithium replenishing cycle.
[0049] In some embodiments, the trajectory of the hole wall in the open-cell structure includes at least one of an open curve and a closed curve.
[0050] In this article, an open curve refers to a curve whose two endpoints do not coincide, that is, the curve has a clear starting point and an end point in a plane and does not form a closed figure. As an example, an open curve can be at least one of a line segment, a ray, a hyperbola, a parabola, and any irregular curve.
[0051] In this article, a closed curve refers to a curve whose starting point and end point coincide with each other, forming a closed figure that encloses a part of a plane. As an example, the closed curve can be at least one of a circle, an ellipse, a polygon, and an irregular figure.
[0052] The trajectory of the pore wall in the open-pore structure is an open curve. At this time, lithium ions have abundant transmission paths, thereby increasing the diffusion rate of lithium ions. This not only enables the lithium ions between the composite solid electrolyte and the positive electrode material to migrate quickly, but also enables the lithium replenishment material to fully exert its lithium replenishment performance and improve the lithium replenishment efficiency. At the same time, the open-pore structure can also buffer the stress caused by the volume change of the positive electrode material to a certain extent, thereby improving the stability of the battery.
[0053] The trajectory of the pore wall in the open-pore structure is a closed curve. At this time, the open-pore structure can form a complete encirclement, thereby effectively improving the contact effect between the positive electrode material and the open-pore structure, that is, the composite solid electrolyte, so that the lithium ions have a higher transmission rate, and the battery's charge and discharge capacity and energy density are improved. In addition, the closed curve trajectory is conducive to the formation of ion circulation inside the composite solid electrolyte, which helps to reduce the accumulation of lithium ions in local areas and concentration polarization, and improve the battery's charge and discharge efficiency and cycle life.
[0054] See also Figure 3 , Figure 3 Schematic diagram of the trajectory of an open-cell structure as an example. Figure 3 The trajectory shown in A in FIG. 1 is an example of an open curve, and the open hole structure presents a spiral shape. Figure 3 The trajectory shown in B is also an example of an open curve. Figure 3 The trajectory shown by C in FIG. 1 is an example of a closed curve.
[0055] In some embodiments, the open pore structure includes a sub-open pore structure, and the sub-open pore structure is a two-dimensional spiral structure.
[0056] In the text, a two-dimensional spiral structure can be a structure that continuously bends and extends around a center point in a certain rotation direction (clockwise or counterclockwise) on a plane. As an example, a two-dimensional spiral structure includes but is not limited to at least one of a circular two-dimensional spiral structure, a square two-dimensional spiral structure, a polygonal two-dimensional spiral structure, and an elliptical two-dimensional spiral structure. Of course, the shape of the two-dimensional spiral structure can be different. From the overall appearance, it is a spiral path composed of different geometric shapes. For example, starting from a center of a circle, it is first a circular trajectory. When this circular trajectory completes a circle, the next circle can be a square shape that spirals outward, and then the next circle turns back to a circle, and so on, forming a two-dimensional spiral structure of mixed shape.
[0057] The lithium replenishment part is set as a two-dimensional spiral structure. On the one hand, it not only provides multi-angle ion diffusion particle diameters and improves the lithium ion transmission rate between the composite solid electrolyte and the positive electrode material, but also the two-dimensional spiral structure has periodicity, so that the solid electrolyte matrix in the open-pore structure can contact the positive electrode material in a relatively stable manner, which is not only conducive to the transmission of lithium ions between the solid electrolyte matrix and the positive electrode material, but also conducive to the lithium ions in the lithium replenishment material to be more evenly replenished to various parts of the positive electrode material, so that the lithium replenishment process is more uniform; on the other hand, the two-dimensional spiral structure shortens the transmission distance of lithium ions, and lithium ions can reach the positive electrode material in a faster time through the spiral path. At the same time, the two-dimensional spiral structure can also guide lithium ions to be transmitted more orderly in the solid electrolyte matrix, reducing the transmission resistance of lithium ions, thereby significantly improving the charge and discharge performance and energy density of the battery; on the other hand, the two-dimensional spiral structure increases the contact area between the solid electrolyte matrix and the positive electrode material in a winding manner, which is conducive to the exchange of lithium ions between the two, and can also alleviate the interface stress generated by the volume change of the positive electrode material to a certain extent, thereby maintaining a good contact state to improve the electrochemical performance of the battery.
[0058] In some embodiments, the parameters of the two-dimensional spiral structure are: a height of 100 μm-200 μm, a width of 50 μm-150 μm, and a spacing between adjacent threads of 40 μm-250 μm.
[0059] For example, the height may be 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 200 μm, etc. Typical but non-limiting values. The width may be 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, etc. Typical but non-limiting values. The spacing between adjacent threads may be 40 μm, 60 μm, 80 μm, 100 μm, 120 μm, 150 μm, 180 μm, 200 μm, 220 μm, 250 μm, etc. Typical but non-limiting values.
[0060] By controlling the relevant parameters of the two-dimensional spiral structure such as width, height, and interval between adjacent threads within the above range, the solid electrolyte matrix and the positive electrode material have a better contact effect, which not only shortens the lithium ion transmission path between the composite solid electrolyte and the positive electrode material, but also enhances the interface adhesion between the positive electrode material and the electrolyte, thereby effectively improving the lithium ion transmission rate and significantly improving the battery's charge and discharge performance and energy density.
[0061] In some embodiments, the open-pore structure includes a plurality of sub-open-pore structures, the trajectories of any two sub-open-pore structures do not overlap, and the plurality of sub-open-pore structures form at least one of a nested distribution and a discrete distribution.
[0062] See also Figure 3 , Figure 3 Schematic diagram of the trajectory of an open-cell structure as an example. Figure 3 The trajectory shown in A in is the open curve of an example nested distribution, Figure 3 The trajectory shown in B is an example of an open curve for a discrete distribution, Figure 3 The trajectory shown in C is an example of a discrete distribution closed curve.
[0063] Nested distribution means that the graphics formed by any number of sub-opening structures present a positional relationship of layered inclusion, which can be concentric nesting or non-concentric nesting. Exemplarily, when the trajectories of the sub-opening structures are all closed curves such as circles, concentric circle nesting distribution can be formed, or non-concentric circle nesting can be formed, that is, each nested graphic is completely located in the inner area of the graphic that nests it, but does not revolve around a center. Exemplarily, when the trajectories of the sub-opening structures are all open curves such as spirals, the same center of the circle can be used as a reference, and one spiral can be inside or outside another to form a concentric nested distribution, and at the same time, they can also not be nested around a center.
[0064] Multiple sub-opening structures form a nested distribution, thereby forming a multi-level ion conduction channel, reducing the lithium ion transmission path, and thus effectively improving the lithium ion transmission efficiency. This distribution method helps to increase the stability of the contact interface between the solid electrolyte matrix and the positive electrode material, thereby optimizing the ion transmission performance of the interface contact, allowing lithium ions to migrate more smoothly between the solid electrolyte matrix and the positive electrode material, so that the battery exhibits better charge and discharge performance; at the same time, it promotes the lithium de-lithiation process of the lithium replenishment material to achieve efficient lithium replenishment.
[0065] Discrete distribution means that these multiple sub-opening structures are separated from each other in the plane without being tangent or intersecting, and their positions are relatively random or distributed according to a certain pattern.
[0066] Multiple sub-opening structures form a discrete distribution, which can provide multiple independent transmission paths for lithium ions, which helps to improve the continuity and stability of ion transmission. It not only enables lithium ions to migrate more smoothly between the solid electrolyte matrix and the positive electrode material, but also helps the lithium replenishment material to smoothly play its lithium replenishment role.
[0067] In some embodiments, the trajectory of the open-pore structure is an open curve, and the parameters of the sub-open-pore structure are: height of 100 μm-200 μm, width of 50 μm-150 μm, and the shortest distance between any two sub-open-pore structures is 40 μm-300 μm.
[0068] Exemplarily, the height of the sub-opening structure can be typical but non-limiting values such as 100μm, 110μm, 120μm, 130μm, 140μm, 150μm, 160μm, 170μm, 180μm, 190μm, 200μm, etc., the width can be typical but non-limiting values such as 50μm, 70μm, 80μm, 100μm, 120μm, 130μm, 150μm, etc., and the shortest distance between any two sub-opening structures can be typical but non-limiting values such as 40μm, 60μm, 80μm, 100μm, 120μm, 150μm, 180μm, 200μm, 220μm, 250μm, 270μm, 300μm, etc.
[0069] The trajectory of the open-pore structure is an open curve, and the relevant parameters of the sub-open-pore structure are within the above range. Its width range means that a wider ion transmission channel is formed in the solid electrolyte matrix, which is beneficial to improving its ion conductivity; its height means that the solid electrolyte matrix contained in the open-pore structure has a larger contact area with the positive electrode material, shortening the transfer distance of lithium ions from the solid electrolyte matrix to the positive electrode material, and the solid electrolyte matrix has better mechanical strength, so that it can better resist external pressure and internal stress, and improve the structural integrity of the solid electrolyte matrix; the shortest distance between the two means that the relative uniformity of the contact area between the positive electrode material and the solid electrolyte matrix is better, and it is not easy to have too much or too little local positive electrode material.
[0070] In the embodiment of the present application, the shortest distance between any two sub-opening structures refers to the distance between each point in any sub-opening structure to each point in another sub-opening structure, and then the smallest value among these distances is found, which is the shortest distance.
[0071] In some embodiments, the trajectory of the open structure is a closed curve, and the parameters of the sub-opening structure are: height 100μm-180μm, width 50μm-150μm, equivalent ellipse minor axis 45μm-250μm, and the shortest distance between any two sub-opening structures is 40μm-300μm.
[0072] For example, the height of the sub-opening structure can be 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, etc., which are typical but non-limiting values; the width can be 50 μm, 70 μm, 80 μm, 100 μm, 120 μm, 130 μm, 150 μm, etc., which are typical but non-limiting values; the minor axis of the equivalent ellipse can be 45 μm, 70 μm, 1 The shortest distance between any two sub-opening structures can be 40μm, 60μm, 80μm, 100μm, 120μm, 150μm, 180μm, 200μm, 220μm, 250μm, etc., which are typical but non-limiting values; the shortest distance between any two sub-opening structures can be 40μm, 60μm, 80μm, 100μm, 120μm, 150μm, 180μm, 200μm, 220μm, 250μm, 270μm, 300μm, etc., which are typical but non-limiting values.
[0073] In the embodiments of the present application, the minor axis of the equivalent ellipse is a length parameter determined by a specific rule or equivalent method for a geometric figure or physical structure that is not a standard ellipse. Specifically, an ellipse is drawn with the maximum length of the figure as the major axis of the ellipse. The area of the ellipse is equal to the area of the figure. The minor axis of this ellipse is called the minor axis of the equivalent ellipse. In this article, since the sub-opening structure has a certain height, the minor axis of the equivalent ellipse refers to the distance measured in the space enclosed by the sub-opening structure.
[0074] By controlling each parameter within the above range, the sub-open-pore structure has a larger ion transmission flux, better mechanical properties, and significantly increases the contact area and contact stability between the solid electrolyte matrix and the positive electrode material in the open-pore structure.
[0075] In some embodiments, the mass ratio of the solid electrolyte matrix to the lithium supplement material is 1:(0.00005-0.1).
[0076] In some embodiments, the mass ratio of the solid electrolyte matrix to the lithium supplement material is 1:(0.001-0.1).
[0077] For example, the content of the lithium supplement material may be 0.00005, 0.0001, 0.001, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, and other typical non-limiting values.
[0078] Within the above-mentioned ratio range, the lithium-supplementing material can release sufficient lithium ions during the first charge and discharge process of the battery to compensate for the irreversible lithium loss of the positive electrode material in the first cycle, and the lithium-supplementing material can form an appropriate amount of delithiation products, which are fixed in the solid electrolyte matrix to effectively improve the structural integrity of the composite solid electrolyte.
[0079] In some embodiments, the ratio of the side area of the open cell structure to the area of the circumscribed circle of the open cell structure is (10-200): 100. Exemplarily, the ratio of the side area of the open cell structure to the area of the circumscribed circle of the open cell structure can be 100:10, 16:100, 30:100, 50:100, 80:100, 100:100, 130:100, 159:100, 170:100, 180:100, 200:100, etc., which are typical but non-limiting values.
[0080] In some embodiments, the ratio of the side area of the open cell structure to the area of the circumscribed circle of the open cell structure is (90-120): 100. Exemplarily, the ratio of the side area of the open cell structure to the area of the circumscribed circle of the open cell structure can be 90:100, 100:100, 110:100, 120:100, and other typical but non-limiting values.
[0081] In the embodiments of the present application, the lateral area refers to the area of the open structure along the height direction. Exemplarily, the lateral area of the two-dimensional spiral structure is approximately equal to the height * length, and the length refers to the length formed by the unfolding of the two-dimensional spiral structure. Generally, an image measuring instrument can be used to test the lateral area of the open structure, specifically: using an optical imaging system such as a camera, a scanner, etc. to collect the image of the object into a computer, and then using image processing technology and measurement software (such as ImageJ, Photoshop, etc.) to measure the size and shape of the object in the image, and calculate its lateral area by pixel counting and proportional conversion.
[0082] In the embodiments of the present application, the circumscribed circle refers to the smallest circle that can contain the open-cell structure. For example, the circumscribed circle of a two-dimensional spiral structure refers to a circle constructed with the maximum length of the outermost ring as the diameter, which can surround the two-dimensional spiral structure; the open-cell structure includes multiple sub-open-cell structures, and the circumscribed circle refers to the smallest circle that can contain these figures at the same time, and the circumference of this circle must be tangent to at least some elements of these figures (such as the vertices of polygons, the boundary points of figures, etc.) or contain all the points of these figures.
[0083] It should be noted that the open hole structure is stacked on the surface of the support part, wherein the bottom surface of the open hole structure is completely in contact with the surface of the support part, and the area covered by the circumscribed circle of the open hole structure is also completely contained in the surface area, that is, the area of the circumscribed circle of the open hole structure is less than or equal to the plane area.
[0084] Controlling the ratio of the side area of the open-pore structure to the area of the circumscribed circle of the open-pore structure within the above range means that the open-pore structure has a larger contact area with the positive electrode material, improving the contact effect between the solid electrolyte matrix and the positive electrode material, and increasing the uniformity of the lithium replenishment effect.
[0085] In some embodiments, the composite solid electrolyte further includes a conductive agent, which is distributed in the solid electrolyte matrix, and at least a portion of the conductive agent is in contact with the lithium supplement material.
[0086] Exemplarily, the conductive agent may include, but is not limited to, at least one of superconducting carbon, carbon black (such as acetylene black or Ketjen black), carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0087] The conductive agent has good conductivity and can effectively improve the conductivity of the lithium supplement material, thereby facilitating the lithium supplement material to achieve a better lithium supplement effect.
[0088] In some embodiments, the composite solid electrolyte further includes a conductive agent, and the mass ratio of the solid electrolyte matrix, the lithium supplement material, and the conductive agent is 1:(0.00005-0.1):(0.000005-0.05).
[0089] In some embodiments, the composite solid electrolyte further includes a conductive agent, and the mass ratio of the solid electrolyte matrix, the lithium supplement material, and the conductive agent is 1: (0.001-0.01): (0.0005-0.005).
[0090] Exemplarily, the content of lithium supplement material can be 0.00005, 0.0001, 0.001, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.083, 0.09, 0.1 and other typical but non-limiting values, and the content of conductive agent can be 0.000005, 0.00001, 0.0001, 0.001, 0.002, 0.008, 0.01, 0.012, 0.015, 0.018, 0.02, 0.023, 0.025, 0.028, 0.03, 0.035, 0.04, 0.05 and other typical but non-limiting values.
[0091] Within the above-mentioned proportion range, the lithium-replenishing material can release sufficient lithium ions during the first charge and discharge process of the battery to compensate for the irreversible lithium loss of the positive electrode material in the first cycle; the solid electrolyte matrix can construct a continuous and stable ion transmission channel, so that a stable conductive path is formed inside the battery, promoting the smooth operation of the battery, and can also fix the lithium-replenishing material therein, thereby helping to improve the lithium-replenishing efficiency and capacity utilization of the lithium-replenishing material; the conductive agent can reduce the resistance of electron transmission in the solid electrolyte matrix, thereby further promoting the lithium-replenishing material delithiation process.
[0092] In some embodiments, the solid electrolyte matrix includes at least one of a polymer solid electrolyte and an oxide solid electrolyte.
[0093] These solid electrolyte matrices have good ionic conductivity and good toughness, which allows them to move and rearrange to a certain extent when the temperature fluctuates or the internal pressure of the battery changes. That is, the solid electrolyte matrix, driven by toughness, can fill the pits or gaps produced by the decomposition of the lithium replenishing material, which helps to improve the structural stability of the composite solid electrolyte and the lithium replenishing effect.
[0094] Exemplarily, the oxide electrolyte includes at least one of a perovskite solid electrolyte, a sodium superionic conductor solid electrolyte (NASICON), a lithium superionic conductor solid electrolyte (LISICON), and a lithium lanthanum zirconium oxygen solid electrolyte (LLZO).
[0095] In some embodiments, the solid electrolyte matrix includes a polymer solid electrolyte.
[0096] The lithium-replenishing material is mixed in the solid electrolyte matrix. Therefore, the lithium-depleting products of the lithium-replenishing material, such as inorganic fillers, are also distributed in the solid electrolyte matrix. The addition of inorganic fillers can not only effectively reduce the crystallinity of the polymer solid electrolyte, making the arrangement of the polymer chains relatively loose, which provides more free space and relatively continuous transmission channels for lithium ions, but also effectively increase the mobility of the polymer solid electrolyte, creating a more favorable transmission environment for lithium ions, thereby significantly increasing the ionic conductivity of the solid electrolyte matrix; in addition, the inorganic filler itself has good mechanical properties, which significantly enhances the mechanical properties of the solid electrolyte matrix, which effectively improves the stability of the overall structure of the solid electrolyte matrix.
[0097] Exemplarily, the polymer solid electrolyte includes, but is not limited to, a polyethylene oxide (PEO)-based polymer solid electrolyte.
[0098] PEO-based polymer solid electrolytes have good electrode compatibility and good solubility in positive electrode materials, which helps to reduce the interfacial impedance between the positive electrode material and the solid electrolyte matrix. PEO-based polymer solid electrolytes have good toughness and film-forming properties. During the battery cycle, driven by their own toughness, they can fill the pits or gaps produced by the decomposition of lithium-supplementing materials, thereby forming a continuous and stable ion conduction path in the solid electrolyte matrix. In addition, PEO-based polymer solid electrolytes have good thermal stability and a wide electrochemical window, which enables them to maintain good ionic conductivity and mechanical properties under high temperature and high pressure, thereby improving the safety and reliability of the battery.
[0099] Exemplarily, the viscosity average molecular weight of the PEO-based polymer solid electrolyte is 500,000-1,000,000.
[0100] The full name of viscosity average molecular weight is viscosity average molecular weight, which is the molecular weight of the polymer measured by dilute solution viscosity method.
[0101] In some embodiments, the solid electrolyte matrix further includes a plasticizer. Exemplarily, the plasticizer includes but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), phthalate compounds, and plastic crystals (such as amber crystals).
[0102] A second aspect of the embodiment of the present application provides a method for preparing a composite solid electrolyte, comprising the following steps:
[0103] Step S10, preparing an electrolyte slurry containing a lithium supplement material and a solid electrolyte matrix precursor;
[0104] Step S20, curing the electrolyte slurry so that the lithium supplement material is distributed in the solid electrolyte matrix and forms a preset shape, thereby obtaining a composite solid electrolyte.
[0105] The second aspect of the present application embodiment provides a method for preparing a composite solid electrolyte, which mixes a lithium-replenishing material with a solid electrolyte matrix precursor to form an electrolyte slurry. During the curing process, the lithium-replenishing material is mixed into the solid electrolyte matrix and formed into a preset shape, thereby effectively preparing a composite solid electrolyte having the properties as described above in the present application.
[0106] In some embodiments, in step S10, the selection of lithium supplementing material is as described above and will not be repeated herein.
[0107] In some embodiments, in step S10, the solid electrolyte matrix formed includes at least one of a polymer solid electrolyte matrix and an oxide solid electrolyte matrix, and the solid electrolyte matrix precursor here refers to a substance used to form a polymer solid electrolyte matrix and an oxide solid electrolyte matrix.
[0108] Exemplarily, the precursor of the polymer solid electrolyte matrix includes a first cross-linking agent, a first photoinitiator, a first plasticizer and a first lithium salt, wherein the mass ratio of the first cross-linking agent, the first plasticizer and the first lithium salt is 0.8-2.5:1:0.8-2, the mass ratio of the first photoinitiator to the first cross-linking agent is 1-3wt%, and the molar ratio of the number of monomers in the first cross-linking agent to the lithium ions in the first lithium salt is 5-32:1.
[0109] Under the action of the photoinitiator, the cross-linking agent undergoes free radical polymerization and cross-linking polymerization to form a polymer. The plasticizer molecules will be inserted between the polymer molecular chains, weakening the interaction between the polymer molecular chains and increasing the activity of the molecular chains, thereby playing a plasticizing role. The lithium salt interacts with specific functional groups in the polymer (such as functional groups containing oxygen atoms) to form ion conduction channels, which makes the polymer material have the function of an electrolyte, thereby obtaining a polymer solid electrolyte with higher ion conductivity performance.
[0110] Exemplarily, the first cross-linking agent includes, but is not limited to, at least one of polyethylene glycol diacrylate, acrylate, and methacrylate.
[0111] Exemplarily, the first photoinitiator includes, but is not limited to, at least one of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (photoinitiator 819), trimethylbenzoyl-diphenylphosphine oxide (TPO) and 2-hydroxy-2-methyl-1-phenyl-1-propanone (HMPF).
[0112] Exemplarily, the first plasticizer includes, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), phthalate compounds, and plastic crystals (such as amber crystals).
[0113] Exemplarily, the first lithium salt includes, but is not limited to, at least one of LiClO4, LiAsF4, LiPF6, LiBF4 and LiTFSI.
[0114] Exemplarily, the electrolyte slurry also includes a conductive agent, and the mass ratio of the first cross-linking agent: the lithium supplementing material: the conductive agent is (0.2-0.6): (0.00005-0.1): (0.000005-0.05).
[0115] In some embodiments, in step S10, the specific process of preparing the electrolyte slurry containing the lithium supplement material and the solid electrolyte matrix precursor is as follows:
[0116] The lithium supplement material, the solid electrolyte matrix precursor and the conductive agent are mixed, and stirred at a rotation speed of 800 rpm to 2000 rpm for 5 min to 20 min.
[0117] For example, the stirring process may be performed using a THINKY mixer.
[0118] In some embodiments, before the electrolyte slurry is solidified, the following steps are included:
[0119] Step S11, preparing a second slurry containing a solid electrolyte matrix precursor, and curing the second slurry to obtain a support portion of the composite solid electrolyte.
[0120] The solid electrolyte matrix of the formed support composite solid electrolyte includes at least one of a polymer solid electrolyte matrix and an oxide solid electrolyte matrix. Here, the solid electrolyte matrix precursor refers to a substance used to form a polymer solid electrolyte matrix and an oxide solid electrolyte matrix.
[0121] Exemplarily, the precursor of the solid electrolyte matrix of the supporting portion composite solid electrolyte includes a second cross-linking agent, a second photoinitiator, a second plasticizer and a second lithium salt, wherein the mass ratio of the second cross-linking agent, the second plasticizer and the second lithium salt is 0.8-2.5:1:0.8-2, the mass ratio of the second photoinitiator to the second cross-linking agent is 1-3wt%, and the molar ratio of the number of monomers in the second cross-linking agent to the lithium ions in the second lithium salt is 5-32:1.
[0122] Exemplarily, the second cross-linking agent includes, but is not limited to, at least one of polyethylene glycol diacrylate, acrylate, and methacrylate.
[0123] Exemplarily, the second photoinitiator includes, but is not limited to, at least one of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (photoinitiator 819), trimethylbenzoyl-diphenylphosphine oxide (TPO) and 2-hydroxy-2-methyl-1-phenyl-1-propanone (HMPF).
[0124] Exemplarily, the second plasticizer includes, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), phthalate compounds, and plastic crystals (such as amber crystals).
[0125] Exemplarily, the second lithium salt includes, but is not limited to, at least one of LiClO4, LiAsF4, LiPF6, LiBF4 and LiTFSI.
[0126] In some embodiments, in step S11, the specific process of preparing the second slurry containing the solid electrolyte matrix precursor is as follows:
[0127] The solid electrolyte matrix precursors are mixed and stirred at a rotation speed of 800 rpm to 2000 rpm for 5 min to 20 min.
[0128] For example, the stirring process may be performed using a THINKY mixer.
[0129] In some embodiments, in step S11 , the curing process may be performed using a stereolithography method.
[0130] Exemplary conditions for stereolithography include: humidity of 0-40%, laser wavelength of 350nm-450nm, power of 5-15W / cm 2 .
[0131] In some embodiments, in step S11, the curing treatment also includes a hardening treatment, and the hardening treatment includes: first treating at 25°C-45°C for 1h-6h, and then treating at 25°C-45°C for 48h-60h in an inert atmosphere with a water content of <1ppm.
[0132] It should be pointed out that after the support portion is formed as one piece, its preset shape presents two opposite planes, there is a certain thickness between the two planes, the thickness direction is perpendicular to the two planes, and the area of the plane is greater than or equal to the circumscribed circle area of the opening structure.
[0133] In some embodiments, the thickness of the support portion is 60 μm-150 μm. For example, the thickness of the support portion can be 60 μm, 80 μm, 90 μm, 100 μm, 120 μm, 150 μm, etc., which are typical but non-limiting values.
[0134] Within this height range, it means that lithium ions have a suitable transmission path and a lower transmission internal resistance between the positive and negative electrodes, so that lithium ions can be transmitted in the battery at a faster speed, so that the secondary battery has a better capacity retention rate and charge and discharge performance.
[0135] In some embodiments, in step S20, the specific process of curing the electrolyte slurry is:
[0136] The electrolyte slurry is cured on any surface of the support portion, and the curing process can be performed by stereolithography.
[0137] Exemplary conditions for stereolithography include: humidity of 0-40%, laser wavelength of 350nm-450nm, power of 5-15W / cm 2 .
[0138] In some embodiments, in step S20, the curing treatment also includes a hardening treatment, and the hardening treatment includes: first treating at 25°C-45°C for 1h-6h, and then treating at 25°C-45°C for 48h-60h in an inert atmosphere with a water content of <1ppm.
[0139] A third aspect of an embodiment of the present application provides a secondary battery, comprising a positive electrode material, a negative electrode material and a solid electrolyte layer, wherein the solid electrolyte layer comprises the composite solid electrolyte provided in the first aspect or the composite solid electrolyte obtained by the preparation method provided in the second aspect.
[0140] The secondary battery provided in the third aspect of the embodiment of the present application contains the composite solid electrolyte of the present application, so that the obtained secondary battery has the characteristics of high capacity, high initial efficiency and long cycle, improves the overall electrochemical performance of the battery, and is conducive to wide use.
[0141] In some embodiments, an open-pore structure is formed on one side of the solid electrolyte layer;
[0142] The positive electrode material is arranged on a side of the solid electrolyte layer close to the open-porous structure, and the positive electrode material is filled in the open-porous structure and / or dispersed around the open-porous structure.
[0143] Since the composite solid electrolyte includes a support portion and a lithium replenishing portion, and the lithium replenishing portion can be provided in an open-pore structure, the solid electrolyte layer formed by the composite solid electrolyte has an open-pore structure and a plane relatively provided along the thickness direction.
[0144] In the embodiment of the present application, the positive electrode material is arranged on a side close to the open-pore structure, and the positive electrode material is filled in the open-pore structure and / or dispersed around the open-pore structure, which means that the positive electrode material can form a good contact effect with the solid electrolyte matrix contained in the open-pore structure, thereby effectively improving the lithium ion transmission rate and significantly improving the charging and discharging performance and energy density of the battery. At the same time, the lithium supplement material is fixed in the solid electrolyte matrix, which means that the lithium supplement material and the positive electrode material are separated from each other, so that the delithiation products of the lithium supplement material will not accumulate in the positive electrode material, thereby effectively avoiding the problem of increased impedance of the positive electrode material caused by the delithiation products of the lithium supplement material.
[0145] In some embodiments, the positive electrode material includes a positive electrode active material, which may include a positive electrode active material for a battery known in the art. As examples, the positive electrode active material includes but is not limited to lithium iron phosphate, lithium cobalt oxide (such as LiCoO2), lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.8 Co 0.15 Al 0.05 O2) and its modified compounds, etc.
[0146] In some embodiments, the positive electrode material further includes a conductive agent and a binder.
[0147] Exemplarily, the conductive agent in the positive electrode material includes, but is not limited to, one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60 and carbon nanotubes. Exemplarily, the binder in the positive electrode material includes, but is not limited to, one or more of solid electrolyte-lithium salt complex, polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan and chitosan derivatives.
[0148] As an example, the solid electrolyte in the solid electrolyte-lithium salt composite includes at least one of a sulfide solid electrolyte, an oxide electrolyte, and a polymer solid electrolyte, and the polymer solid electrolyte includes but is not limited to a PEO-based polymer solid electrolyte.
[0149] As an example, the lithium salt in the solid electrolyte-lithium salt composite includes, but is not limited to, at least one of LiClO4, LiAsF4, LiPF6, LiBF4 and LiTFSI.
[0150] As an example, the solid electrolyte-lithium salt complex includes but is not limited to a PEO-based polymer solid electrolyte-LiClO4 complex, wherein the molar ratio of the monomer contained in the PEO-based polymer to the lithium ion is 5-32:1.
[0151] In some embodiments, the preparation process of the positive electrode sheet in the secondary battery is as follows:
[0152] The positive electrode active material, conductive agent and binder are dispersed in an organic solvent and stirred to obtain positive electrode slurry, and the positive electrode slurry is coated in the open pore structure of the solid electrolyte layer so that the positive electrode slurry fills the open pore structure or is distributed around the open pore structure, and dried to form a positive electrode sheet.
[0153] Since an open-pore structure with a specific shape is formed on one side of the solid electrolyte layer, the positive electrode slurry is coated in the open-pore structure, and after drying, the positive electrode material is filled in the open-pore structure and / or dispersed around the open-pore structure. In this way, there is a better contact effect between the solid electrolyte matrix contained in the solid electrolyte layer and the positive electrode material.
[0154] Exemplarily, the mass ratio of the positive electrode active material, the conductive agent and the binder is 55-65:5-15:25:35.
[0155] Illustratively, the organic solvent includes, but is not limited to, at least one of acetonitrile, acetone, and dimethyl sulfoxide.
[0156] For example, the coating amount of the positive electrode slurry is 1.6-11.7 mg / cm 2 .
[0157] For example, the surface density of the positive electrode sheet is 1-6 mg / cm 2 .
[0158] "Area density" refers to the mass per unit area, usually expressed as weight per unit area (e.g. mg / m 2 、mg / cm 2 、mg / mm 2 ) to indicate.
[0159] In some embodiments, the negative electrode material is disposed on a side of the solid electrolyte layer away from the pore structure.
[0160] In a battery system, the positive electrode and the negative electrode are disposed on both sides of the solid electrolyte layer. Therefore, the negative electrode is disposed on one side of the plane of the solid electrolyte layer, so that lithium ions have a shorter transmission path, thereby improving the charge and discharge performance of the battery.
[0161] In some embodiments, the negative electrode material includes a negative electrode current collector and a negative electrode active material, and the negative electrode active material is coated on the negative electrode current collector. The negative electrode current collector can be at least one of pure lithium, a lithium alloy, and a lithium metal composite oxide. The lithium alloy may include any one or more of aluminum (Al), magnesium (Mg), potassium (K), sodium (Na), calcium (Ca), strontium (Sr), barium (Ba), silicon (Si), germanium (Ge), antimony (Sb), lead (Pb), indium (In), and zinc (Zn). The lithium metal composite oxide may include a composite of lithium and an oxide (MeO x ) of any one metal (Me) selected from silicon (Si), tin (Sn), zinc (Zn), magnesium (Mg), cadmium (Cd), cerium (Ce), nickel (Ni), tungsten (W), and iron (Fe). For example, the lithium metal composite oxide can be Li x Fe2O3 (0 < x ≤ 1) or Li x WO2 (0 < x ≤ 1).
[0162] In some embodiments, the negative electrode material may only include a negative electrode current collector and does not contain a negative electrode active material. Exemplarily, the negative electrode material can be at least one of pure lithium, a lithium alloy, and a lithium metal composite oxide as the negative electrode material.
[0163] In some embodiments, after the secondary battery is subjected to formation treatment, the solid electrolyte layer further includes an inorganic filler, and the inorganic filler is a delithiated product of the lithium supplement material.
[0164] Since the composite solid electrolyte includes a solid electrolyte matrix and a lithium supplement material, and the lithium supplement material is fixed in the solid electrolyte matrix, this means that the delithiated product of the lithium supplement material, such as the inorganic filler, is also fixed and distributed in the solid electrolyte matrix. These inorganic fillers can form a reinforcing network inside the solid electrolyte matrix, thereby better maintaining the structural integrity of the solid electrolyte matrix, which helps the composite solid electrolyte to play the role of ion conduction and separating the positive and negative electrodes.
[0165] In some embodiments, the ionic conductivity of the solid electrolyte layer ranges from 1×10 -5 -9.5×10 -3 S / cm.
[0166] Since the lithium-replenishing material is mixed in the solid electrolyte matrix, the lithium-depletion products of the lithium-replenishing material, such as inorganic fillers, are also distributed in the solid electrolyte matrix. The addition of inorganic fillers can not only effectively reduce the crystallinity of the polymer solid electrolyte, making the arrangement of the polymer chains relatively loose, which provides more free space and relatively continuous transmission channels for lithium ions, but also effectively increase the mobility of the polymer solid electrolyte, creating a more favorable transmission environment for lithium ions, thereby significantly increasing the ionic conductivity of the solid electrolyte matrix.
[0167] The following is a description of the composite solid electrolyte, preparation method, and application of the present invention through a number of specific embodiments.
[0168] Example 1
[0169] This embodiment provides a composite solid electrolyte and a secondary battery.
[0170] Composite solid electrolyte
[0171] The composite solid electrolyte includes a supporting part and a lithium replenishing part stacked on the surface of the supporting part. The supporting part only contains a solid electrolyte matrix (PEO-based solid electrolyte), has a thickness of 100 μm, and a circular cross-section with a diameter of 19 mm; the lithium replenishing part is an open-pore structure, that is, the supporting part has a first surface and a second surface arranged opposite to each other along the thickness direction, and a lithium replenishing part with an open-pore structure (two-dimensional spiral structure) is arranged on the first surface. The ratio of the side area of the open-pore structure to the area of the circumscribed circle of the open-pore structure is 80:100. The lithium replenishing part includes a solid electrolyte matrix (PEO-based solid electrolyte), a lithium replenishing material (Li6CoO4) and a conductive agent (carbon black) in a mass ratio of 1:0.005:0.0008. The lithium replenishing material and the conductive agent are mixed in the solid electrolyte matrix. The parameters of the two-dimensional spiral structure are: height is 150 μm, width is 80 μm, and the interval between adjacent threads is 60 μm.
[0172] Secondary battery
[0173] [Preparation of solid electrolyte layer]
[0174] The second crosslinking agent (polyethylene glycol diacrylate, number average molecular weight of 400-1000), the second plasticizer (succinonitrile) and the second lithium salt (LiTFSI) were weighed according to the mass ratio of 2.1:1:0.9, and then the second photoinitiator (phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide) was weighed. The mass ratio of the second photoinitiator to the second crosslinking agent was 3:100. After mixing the above components, they were added to a THINKY mixer and stirred at a speed of 1500 rpm / min for 10 minutes. Then, under the condition of 20% humidity, a laser with a wavelength of 355 nm was used at 10 W / cm 2Stereolithography was performed under power conditions, and finally placed at 30°C for 6 hours, and dried in a glove box with a nitrogen atmosphere with a water content of <0.1ppm for 48 hours to obtain a support portion with a thickness of 100μm, wherein the cross-sectional shape of the support portion is circular and the diameter is 19mm.
[0175] The first cross-linking agent (polyethylene glycol diacrylate, number average molecular weight of 400-1000), the first plasticizer (succinonitrile) and the first lithium salt (LiTFSI) were weighed according to the mass ratio of 2.1:1:0.9, and then the first photoinitiator (phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide) was weighed, and the mass ratio of the first photoinitiator to the first cross-linking agent was 3:100. Finally, the first lithium supplement material (Li6CoO4) and the conductive agent (carbon black) were weighed, and the mass ratio of the first cross-linking agent: lithium supplement material: conductive agent was 0.53:0.005:0.0008. After mixing the above components, they were added to the THINKY mixer and stirred at a speed of 1500rpm / min for 10min. Then, under the condition of 20% humidity, a laser with a wavelength of 355nm was used at 10W / cm 2 Under power conditions, stereolithography is performed on one surface of the support part to form a lithium replenishing part according to a preset shape (two-dimensional spiral structure with a height of 150 μm, a width of 80 μm, and a spacing of 60 μm between adjacent threads). Finally, it is placed at 30°C for 6 hours and dried in a glove box with a nitrogen atmosphere with a water content of <0.1 ppm for 48 hours to obtain a solid electrolyte layer.
[0176] [Preparation of positive electrode sheet]
[0177] The positive electrode active material (lithium iron phosphate), conductive agent (super-P) and binder (PEO-LiTFSI, monomer EO and Li + The molar ratio of the reaction mixture is 15:1) and added to N-methyl-2-pyrrolidone (NMP) at a mass ratio of 6:1:3, and the mixture is stirred for 12 hours to obtain a positive electrode slurry. The positive electrode slurry is coated on the two-dimensional spiral structure of the solid electrolyte layer, and the mixture is dried in a vacuum oven at 40°C for 24 hours, and dried in a glove box with an argon atmosphere for 48 hours to obtain a positive electrode sheet.
[0178] [Preparation of negative electrode sheet]
[0179] Lithium sheet is used as negative electrode.
[0180] [Preparation of Secondary Battery]
[0181] The negative electrode sheet was placed on one side of the solid electrolyte layer plane, pressurized at 500 MPa for 5 minutes, and assembled into a secondary battery.
[0182] Example 2
[0183] This embodiment provides a composite solid electrolyte and a secondary battery. The difference from Embodiment 1 is that the solid electrolyte layer is different, specifically, the content of lithium replenishing material in the lithium replenishing part of the solid electrolyte layer is different, and the mass ratio of the solid electrolyte matrix, the lithium replenishing material and the conductive agent is 1:0.001:0.0008.
[0184] Example 3
[0185] This embodiment provides a composite solid electrolyte and a secondary battery. The difference from Embodiment 1 is that the solid electrolyte layer is different, specifically, the content of lithium replenishing material in the lithium replenishing part of the solid electrolyte layer is different, and the mass ratio of the solid electrolyte matrix, the lithium replenishing material and the conductive agent is 1:0.01:0.0008.
[0186] Example 4
[0187] This embodiment provides a composite solid electrolyte and a secondary battery. The difference from Embodiment 1 is that the solid electrolyte layer is different, specifically, the content of the conductive agent in the lithium replenishing part of the solid electrolyte layer is different, and the mass ratio of the solid electrolyte matrix, the lithium replenishing material and the conductive agent is 1:0.005:0.00005.
[0188] Example 5
[0189] This embodiment provides a composite solid electrolyte and a secondary battery. The difference from Embodiment 1 is that the solid electrolyte layer is different, specifically, the content of the conductive agent in the lithium replenishing part of the solid electrolyte layer is different, and the mass ratio of the solid electrolyte matrix, the lithium replenishing material and the conductive agent is 1:0.005:0.003.
[0190] Example 6
[0191] This embodiment provides a composite solid electrolyte and a secondary battery, which differ from Embodiment 1 in that the ratio of the side area of the open hole structure to the area of the circumscribed circle of the open hole structure is 130:100.
[0192] Example 7
[0193] This embodiment provides a composite solid electrolyte and a secondary battery, which differ from Embodiment 1 in that the ratio of the side area of the open hole structure to the area of the circumscribed circle of the open hole structure is 40:100.
[0194] Example 8
[0195] This embodiment provides a composite solid electrolyte and a secondary battery, which differs from Embodiment 1 in that:
[0196] The structures of composite solid electrolytes are different.
[0197] Composite solid electrolyte
[0198] The composite solid electrolyte includes a supporting part and a lithium replenishing part stacked on the surface of the supporting part. The supporting part only contains a solid electrolyte matrix (PEO-based solid electrolyte), whose thickness is 100μm and whose cross-section is a circle with a diameter of 19mm. The lithium replenishing part is arranged in a plane, that is, the thickness of the lithium replenishing part is 100μm and its cross-section is a circle with a diameter of 19mm. The lithium replenishing part includes a solid electrolyte matrix (PEO-based solid electrolyte) with a ratio of 1:0.005:0.0008, a lithium replenishing material (Li6CoO4) and a conductive agent (carbon black).
[0199] Secondary battery
[0200] [Preparation of solid electrolyte layer]
[0201] The second crosslinking agent (polyethylene glycol diacrylate, number average molecular weight of 400-1000), the second plasticizer (succinonitrile) and the second lithium salt (LiTFSI) were weighed according to the mass ratio of 2.1:1:0.9, and then the second photoinitiator (phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide) was weighed. The mass ratio of the second photoinitiator to the second crosslinking agent was 3:100. After mixing the above components, they were added to a THINKY mixer and stirred at a speed of 1500 rpm / min for 10 minutes. Then, under the condition of 20% humidity, a laser with a wavelength of 450nm was used at 10W / cm 2 Stereolithography was performed under power conditions, and finally placed at 30°C for 6 hours, and dried in a glove box with a nitrogen atmosphere with a water content of <0.1ppm for 48 hours to obtain a support portion with a thickness of 100μm, wherein the cross-sectional shape of the support portion is circular and the diameter is 19mm.
[0202] The first cross-linking agent (polyethylene glycol diacrylate, number average molecular weight of 400-1000), the first plasticizer (succinonitrile) and the first lithium salt (LiTFSI) were weighed according to the mass ratio of 2.1:1:0.9, and then the first photoinitiator (phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide) was weighed, and the mass ratio of the first photoinitiator to the first cross-linking agent was 3:100. Finally, the first lithium supplement material (Li6CoO4) and the conductive agent (carbon black) were weighed, and the mass ratio of the first cross-linking agent: lithium supplement material: conductive agent was 0.53:0.005:0.0008. After mixing the above components, they were added to the THINKY mixer and stirred at a speed of 1500rpm / min for 10min. Then, under the condition of 20% humidity, a laser with a wavelength of 450nm was used at 10W / cm 2 Under power conditions, a lithium supplement part with a thickness of 100 μm was obtained, wherein the cross-sectional shape of the lithium supplement part was circular and the diameter was 19 mm. Finally, it was placed at 30°C for 6 hours and dried in a glove box with a nitrogen atmosphere with a water content of <0.1 ppm for 48 hours to obtain a solid electrolyte layer.
[0203] Positive electrode
[0204] The positive electrode active material (lithium iron phosphate), conductive agent (super-P) and binder (PEO-LiTFSI, monomer EO and Li + The molar ratio of the reaction mixture is 15:1) and added into N-methyl-2-pyrrolidone (NMP) at a mass ratio of 6:1:3, and stirred for 12 hours to obtain a positive electrode slurry. The positive electrode slurry was coated on a current collector Al foil and dried in a vacuum oven at 120°C for 3 hours to obtain a positive electrode sheet.
[0205] [Preparation of negative electrode sheet]
[0206] Lithium sheet is used as negative electrode.
[0207] [Preparation of Secondary Battery]
[0208] The positive electrode plate is placed on the side of the solid electrolyte layer close to the lithium replenishing part, and the negative electrode plate is placed on the side of the solid electrolyte layer away from the lithium replenishing part. Pressurize at 500 MPa for 5 minutes to assemble a secondary battery.
[0209] Example 9
[0210] The present embodiment provides a composite solid electrolyte and a secondary battery, which differ from Embodiment 1 in that the solid electrolyte layer is different, specifically: the lithium supplement part in the solid electrolyte layer is an open structure, the open pore structure includes a plurality of sub-open pore structures, the plurality of sub-open pore structures form a discrete distribution, and the trajectory of the sub-open pore structure is a line segment, the height of the sub-open pore structure is 200 μm, the width is 120 μm, and the shortest distance between any two sub-open pore structures is 50 μm.
[0211] Example 10
[0212] This embodiment provides a composite solid electrolyte and a secondary battery, which are different from the first embodiment in that the lithium supplement material is different, specifically: the lithium supplement material is Li2NiO2.
[0213] Comparative Example 1
[0214] This comparative example provides a composite solid electrolyte. The difference between Example 1 and Example 1 is that the composite solid electrolyte does not include a lithium supplement material, and the positive electrode sheet includes a lithium supplement material. The preparation process of the positive electrode sheet is as follows:
[0215] The positive electrode active material (lithium iron phosphate), conductive agent (super-P) and binder (PEO-LiTFSI, monomer EO and Li +The molar ratio of the positive electrode active material to the conductive agent and the binder is 6:1:3, and the mass ratio of the positive electrode active material to the lithium supplement material is 100:2.5. The mixture is stirred for 12 hours to obtain a positive electrode slurry. The positive electrode slurry is coated on the two-dimensional spiral structure of the solid electrolyte layer, dried in a vacuum oven at 40°C for 24 hours, and dried in a glove box in a nitrogen atmosphere for 48 hours to obtain a positive electrode sheet.
[0216] Comparative Example 2
[0217] This comparative example provides a composite solid electrolyte. The difference between Example 1 and Example 1 is that the composite solid electrolyte does not include a lithium supplement material, and the positive electrode sheet does not include a lithium supplement material. The preparation process of the positive electrode sheet is as follows:
[0218] The positive electrode active material (lithium iron phosphate), conductive agent (super-P) and binder (PEO-LiTFSI, monomer EO and Li + The molar ratio of the positive electrode active material to the conductive agent and the binder is 6:1:3, and the mixture is stirred for 12 hours to obtain a positive electrode slurry. The positive electrode slurry is coated on the two-dimensional spiral structure of the solid electrolyte layer, and the mixture is dried in a vacuum oven at 40°C for 24 hours, and dried in a glove box in a nitrogen atmosphere for 48 hours to obtain a positive electrode sheet.
[0219] Performance Testing
[0220] (1) Initial charge and discharge capacity
[0221] The test process of the first charge and discharge capacity of 0.05C is as follows:
[0222] The battery cell was charged to 4.2V at a current density of 0.05C, left to stand for 10 minutes, and then discharged to 2.5V at a current density of 0.05C to obtain the first discharge capacity and first charge capacity of the battery. The battery was tested at 25°C, where 1C = 170mA / g.
[0223] (2) First Coulomb efficiency
[0224] The first coulombic efficiency is calculated according to the following formula:
[0225]
[0226] (3) 200-cycle capacity retention rate
[0227] The test process of cycle performance is as follows:
[0228] The battery cell was first charged and discharged at a current density of 0.05C for 3 cycles to obtain the first discharge capacity and the first coulombic efficiency, and then a long cycle test was performed at a current density of 0.1C for 200 cycles to calculate the battery's cycle capacity retention rate. The battery voltage test window is 2.5-4.2V, and the battery is tested at 25°C, where 1C = 170mA / g.
[0229] (4) AC impedance test
[0230] The prepared solid electrolyte was assembled into a symmetrical battery (Li|composite electrolyte membrane|lithium iron phosphate), and the ionic conductivity was measured by electrochemical impedance spectroscopy at a temperature of 25 °C and a frequency range of 0.1 Hz to 10 6 Hz, and the AC amplitude is 10mV. Finally, the impedance of the electrolyte is obtained through fitting.
[0231] (5) Ionic conductivity
[0232] The prepared solid electrolyte was assembled into a symmetrical cell (SS|composite electrolyte membrane|SS, SS is a stainless steel sheet), and the ionic conductivity was measured by electrochemical impedance spectroscopy at a temperature of 25 °C and a frequency range of 0.1 Hz to 10 6 Hz, AC amplitude is 10mV.
[0233] Finally, the impedance of the electrolyte is obtained through fitting, and the ionic conductivity δ is calculated using the following formula.
[0234]
[0235] In the formula, R b is the intrinsic resistance obtained from electrochemical impedance spectroscopy measurement, S is the contact area between the electrolyte and the stainless steel blocking electrode, and l is the thickness of the electrolyte membrane.
[0236] The performance parameters of the battery cells provided in Examples 1-10 and Comparative Examples 1-2 are shown in Table 1.
[0237] Table 1
[0238]
[0239] It can be seen from the test results of Example 1 and Comparative Example 2 in Table 1 that the addition of lithium supplement materials can effectively improve the first cycle charge and discharge capacity of the battery. This is because the lithium supplement material has a higher specific capacity and can make up for the lithium loss caused by SEI formation. At the same time, after two hundred cycles, the discharge specific capacity of Example 1 is 10 mAh / g higher than that of Comparative Example 1, and the discharge specific capacity of Example 1 at 0.2C is 18 mAh / g higher than that of Comparative Example 1. In addition to the improvement of the capacity of the lithium supplement material itself, the decomposition product of the lithium supplement material acts as a filler for the solid electrolyte, which effectively improves the ionic conductivity of the polymer electrolyte, which is beneficial to improving the capacity retention rate and rate performance of the battery. At the same time, the lithium supplement material contained in the solid electrolyte is also beneficial to improving the ionic conductivity of the composite solid electrolyte.
[0240] From the test results of Example 1 and Comparative Example 1 in the table, it can be seen that adding the lithium supplement material directly to the positive electrode material will not affect the first cycle lithium supplement effect of the lithium supplement material. However, the lithium-depleted products in the lithium supplement material are mostly inactive materials, and the volume of the lithium supplement material is reduced. After lithium depletion, pores are easily formed in the positive electrode sheet, which has an adverse effect on the ionic conductivity and electronic conductivity of the positive electrode sheet, resulting in the capacity of Comparative Example 1 after 200 cycles and at 0.2C being significantly lower than that of Example 1.
[0241] It can be seen from Comparative Example 1 and Comparative Example 2 that since the lithium supplement material is added to Comparative Example 1, the first cycle charge and discharge performance is higher than that of Comparative Example 2. However, the lithium supplement material is likely to have an adverse effect on the positive electrode material after lithium removal, resulting in the rate performance of Comparative Example 1 and the cycle performance after 200 cycles being worse than those of Comparative Example 2.
[0242] It can be seen from Examples 1-3 that, within a certain range, the amount of lithium supplement material added is positively correlated with the specific charge capacity of the first cycle of the battery. This is because the lithium supplement material can compensate for the lithium loss caused by the formation of the SEI film.
[0243] It can be seen from Example 1 and Examples 4-5 that the addition of the conductive agent is beneficial to the capacity release and rate performance improvement of the lithium supplement material.
[0244] It can be seen from the combination of Example 1 and Examples 6-7 that the charge and discharge specific capacity of Example 1 is lower than that of Example 6, and the charge and discharge specific capacity of Example 1 is higher than that of Example 7. This is because the lateral area of the open-pore structure is increased, that is, increasing the specific surface area of the composite solid electrolyte is beneficial to shortening the transmission path of lithium ions, thereby improving the battery capacity and rate performance.
[0245] It can be seen from Example 1 and Example 8 that Example 8 has a planar lithium replenishing portion, resulting in a smaller specific surface area of the lithium replenishing portion than that of the lithium replenishing portion in the example, which makes the ionic conductivity and rate performance of Example 1 better than that of Example 8.
[0246] It can be seen from the data of Example 1 and Example 9 that the charge-discharge performance and rate performance of Example 1 and Example 9 are close, indicating that when the specific surface areas are close, the shape of the electrolyte has no significant effect on the battery performance.
[0247] It can be seen from the data of Example 1 and Example 10 that when the amount of lithium supplement material added is the same, the lithium supplement capacity of Example 1 is higher than that of Example 10. Since the theoretical capacity of Li6CoO4 is 977mAh / g and the theoretical capacity of Li2NiO2 is 486mAh / g, it can be explained that the theoretical capacity value of the lithium supplement material is proportional to its lithium supplement capacity.
[0248] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A composite solid electrolyte, characterized in that: It includes a solid electrolyte matrix and a lithium supplement material distributed in the solid electrolyte matrix, wherein the solid electrolyte matrix and the lithium supplement material are combined to form a preset shape; The chemical formula of the lithium supplement material is Li x M y O z , wherein M includes transition metal elements, 1≤x≤8, 0<y, 0<z<7.
2. The composite solid electrolyte according to claim 1, characterized in that The composite solid electrolyte is divided into a supporting portion and a lithium replenishing portion where the lithium replenishing material is distributed, and the lithium replenishing portion and the supporting portion are stacked on each other; and / or The mass ratio of the solid electrolyte matrix to the lithium supplement material is 1:(0.00005-0.1).
3. The composite solid electrolyte according to claim 2, characterized in that The lithium supplement part is an open-pore structure; and / or, The ratio of the side area of the lithium replenishing portion to the area of the circumscribed circle of the lithium replenishing portion is (10-200):
100.
4. The composite solid electrolyte according to any one of claims 1 to 3, characterized in that The composite solid electrolyte further comprises a conductive agent, the conductive agent is distributed in the solid electrolyte matrix, and at least a portion of the conductive agent is in contact with the lithium supplement material; and / or, The solid electrolyte matrix includes at least one of a polymer solid electrolyte and an oxide solid electrolyte.
5. A method for preparing a composite solid electrolyte, characterized in that: The following steps are involved: preparing an electrolyte slurry containing a lithium supplement material and a solid electrolyte matrix precursor; The electrolyte slurry is solidified so that the lithium supplement material is distributed in the solid electrolyte matrix and forms a preset shape, thereby obtaining a composite solid electrolyte.
6. A secondary battery comprising a positive electrode material, a negative electrode material and a solid electrolyte layer, characterized in that: The solid electrolyte layer comprises the composite solid electrolyte according to any one of claims 1 to 4 or the composite solid electrolyte obtained by the preparation method of claim 5.
7. The secondary battery according to claim 6, characterized in that: An open-pore structure is formed on one side of the solid electrolyte layer; The positive electrode material is arranged on a side of the solid electrolyte layer close to the open-pored structure, and the positive electrode material is filled in the open-pored structure and / or dispersed around the open-pored structure.
8. The secondary battery according to claim 6, wherein: The negative electrode material is arranged on a side of the solid electrolyte layer away from the open pore structure.
9. The secondary battery according to any one of claims 6 to 8, characterized in that: After the secondary battery is subjected to formation treatment, the solid electrolyte layer further comprises an inorganic filler, and the inorganic filler is a delithiation product of the lithium supplement material.
10. The secondary battery according to any one of claims 6 to 8, characterized in that: The ionic conductivity of the solid electrolyte layer is in the range of 1×10 -5 -9.5×10 -3 S / cm.